Pengangkutan Melalui Laut - Sendy Anantyo, Herman Susetyo, Budiharto (Diponegoro Law Journal, 2012)
The presence of adult sea freight is growing widely in many aspects of life, not least in terms of the implementation of the transport of cargo. This is shown by the growing demand for sea freight as the rapid movement of factors of production, the more necessary means of transport vessels connecting inter-island transportation costs are relatively cheap and able to haul stuff in a lot of weight and volume as well as. In this case the carrier responsible for the safety and security of goods that he brought the goods in accordance with the type and amount stated in the document content and/or agreement or contract of carriage that has been organized according to legal sources in Indonesia sea transport arrangements and internationally. Responsibility incurred as a result of the operation of the ship, a destroyed, lost, or damaged goods transported, passenger transport delays and/or goods transported. Therefore, the liability carrier required a legal protection for the sender or recipient of goods to protect the rights and interests, both litigation and non-litigation.